2004
DOI: 10.1577/t03-048.1
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Constraints on Spawning Depth of Yellow Perch: The Roles of Low Temperature and High Solar Ultraviolet Radiation

Abstract: The roles of temperature and ultraviolet radiation (UVR) in determining the spawning success of yellow perch Perca flavescens were investigated in two Pennsylvania lakes with different dissolved organic carbon (DOC) concentrations. In situ incubation experiments were used to manipulate temperature and UVR and to examine hatching time and hatching success. Extensive scuba surveys were used to document actual spawning depths. Differences in the temperature and UVR profiles of the two lakes led to contrasting res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
62
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 27 publications
4
62
0
Order By: Relevance
“…The present study focused on the location and timing of the deposition of egg strands by perch in the newly created Chabařovice Lake. In this lake, Čech et al (2009, 2010) have previously reported that 92% (year 2007) and 88% (2008) of egg strands were deposited at depths greater than 3 m which closely resembles the situation in the low-DOC Lake Giles, Pennsylvania, described by Huff et al (2004;92% of egg strands were deposited at depths greater than 3 m). In Chabařovice Lake, the concentration of DOC has never been analyzed.…”
Section: Introductionsupporting
confidence: 68%
See 4 more Smart Citations
“…The present study focused on the location and timing of the deposition of egg strands by perch in the newly created Chabařovice Lake. In this lake, Čech et al (2009, 2010) have previously reported that 92% (year 2007) and 88% (2008) of egg strands were deposited at depths greater than 3 m which closely resembles the situation in the low-DOC Lake Giles, Pennsylvania, described by Huff et al (2004;92% of egg strands were deposited at depths greater than 3 m). In Chabařovice Lake, the concentration of DOC has never been analyzed.…”
Section: Introductionsupporting
confidence: 68%
“…The mean concentration of DOC in the lake was 6.2 mg · L −1 (min.-max., 5.7-7.6 mg · L −1 ) indicating that according to the classification of Huff et al (2004) Chabařovice Lake belongs to the category of higher-DOC lakes, i.e. to the category where DOC (penetrating UVR in fact) is not responsible for deep deposition of egg strands of perch.…”
Section: Figure 4 Depth Distributions Of Egg Strands Of Perch In Chabmentioning
confidence: 99%
See 3 more Smart Citations